Cognitive dysfunction and negative symptoms in patients with schizophrenia and their first-degree relatives from simplex and multiplex families - Zhang, Zhikun (Neuropsychiatr Dis Treat, 2018)
PURPOSE: This study aimed to investigate cognitive functioning, negative symptoms, and the relationships in schizophrenia (SP) pedigrees and to explore the effect of genetic loading on those endophenotypes. PATIENTS AND METHODS: Forty-four patients with SP, 81 first-degree non-psychotic relatives of patients from simplex and multiplex families, 14 matched control probands, and 29 first-degree relatives of the patients from communities were assessed by the vocabulary subtest (VS) of Wechsler Adult Intelligence Scale, memory span subtests of the Multiple Memory Assessment Scale (MMAS), Wisconsin Card Sorting Test (WCST), Continuous Performance Test (CPT), and Negative Scale of Positive and Negative Syndrome Scale. RESULTS: Compared with controls, patients with SP and their relatives had worse performances in WCST and CPT, and more serious negative symptoms. Patients from multiple families performed poorly on most tests while patients from simplex families had impairments only on the parameters of CPT and WSCT as compared to control probands. Patients from multiple families differed significantly from the patients from simplex families in the digit span and word span of MMAS. After controlling for education, in comparison with relatives of control probands, relatives from multiple families showed impairments in VS, multiple domains of CPT, whereas relatives from simplex families had lower scores on the VS and more total cards and random errors in WSCT. The performances of most tests were linked to negative symptoms in patients with SP. For patients with SP, VS, correct numbers and categories in the WCST, and visual and acoustic errors in the CPT predicted 68.8% of the variability in negative symptoms. CONCLUSION: Our findings support that cognitive deficits and negative symptoms may be markers of hereditary susceptibility of SP and aggravate as the degree of genetic load increases. There are certain relationships between cognitive deficits and negative symptoms in patients with SP.